Different dung beetle diversity patterns emerge from overlapping biotas in a large mountain range of the Mexican Transition Zone. (28th February 2021) - Joaqui, Tatiana; Cultid‐Medina, Carlos A.; Dáttilo, Wesley; Escobar, Federico
Abstract: Aim: Different patterns of the species richness‐elevation relationship have been detected on mountains, however how these arise is unclear. Some patterns may be related to two different colonization processes: Lineages colonizing from adjacent lowlands (a 'vertical' model) or from different latitudes (a 'horizontal' model), or both. We aimed to test whether the predictions of the vertical and horizontal colonization models depend on the biogeographic affinity of species along an elevation gradient. Location: Mexican Transition Zone. Taxon: Neotropical and Holarctic dung beetles. Methods: We sampled at 28 sites along an elevation gradient between 200 and 3450 m a.s.l. We assessed potential different shapes in the models describing the relationships between elevation and species richness, pooling all species together and also according to their biogeographic affinity (Neotropical, Holarctic). Moreover we used additive partitioning of beta‐diversity to investigate the changes in species composition along the elevation gradient, disentangling the contribution of richness differences and spatial replacement. Results: For all species together a mid‐plateau pattern between 1200 and 2200 m a.s.l was observed. Neotropical species decreased rapidly with elevation, while Holarctic species showed a mid–elevation peak at 2500 m a.s.l. We detected three groups of elevations based on species composition, with faunal mixing of Neotropical and Holarctic species in the middle zone of the elevation gradient. We found that richness differences and spatial replacement explained changes in species composition. However, the contribution of both beta diversity components depended on the biogeographic affinity of the species. Main conclusions: Dung beetle diversity patterns are related to the biogeographic affinity of the species. The mid‐plateau pattern is the result of the mixture of Holarctic and Neotropical species in the middle of the elevation gradient. We were able to demonstrate the importance of the use of species' biogeographic affinities in mountain diversity studies.